Analysis of Lesson Five. Elevent Fragment of Analysis of Fourth Grade Students’ Book based on 2013 Curriculum Theme Pahlawanku Subtheme Pahlawanku Kebanggaanku - bernadine ajeng indriasari (LPPM Universitas Negeri Jakarta, 2022)
The aim of this research is to know suitability of fourth grade students’ book based on 2013 Curriculum theme Pahlawanku Subtheme Pahlawanku Kebanggaanku on lesson five with core competencies, learning objectives, indicators, materials, tool and learning resources. This section is eleventh fragment of eighteen fragment of analysis of fourth grade students’ book on theme Pahlawanku. This research using qualitative descriptive method. Which analyze students’ book on fourth grade.then discussing the suitability according with the rule of Ministry of Education and Culture and the implementation of Curriculum 2013. The result showed that 1) lesson five corresponding with core competencies; 2) there is indicator on lesson five to narrow for PPKN subject; 3) lesson five corresponding with learning objectives; 4) there is learning activity not corresponding on lesson five; 5) there is some materials to narrow on lesson five; and 6) lesson five corresponding with tools and learning resources.